Short-term inflation projections model and its assessment in Latvia - Andrejs Bessonovs; Olegs Krasnopjorovs (Baltic Journal of Economics, 2021)
This paper builds a short-term inflation projections (STIP) model for Latvia. The model is designed to forecast highly disaggregated consumer prices using cointegrated ARDL approach of [Pesaran, M., & Shin, Y. (1998). An Autoregressive Distributed Lag Modelling Approach to Cointegration Analysis. Econometric Society Monographs, 31, 371-413.]. We assess the forecast accuracy of STIP model using out-of-sample forecast exercise and show that our model outperforms both aggregated and disaggregated AR(1) benchmarks. Across inflation components, the forecast accuracy gains are 20-30% forecasting 3 months ahead and 15-55% forecasting 12 months ahead.
Keywords: C32; C51; C52; C53; E31; 330; autoregressive distributed lag model; disaggregated approach; food commodity prices; Inflation forecasting; labour costs; oil prices